Early and parallel processing of pragmatic and semantic information in speech acts: neurophysiological evidence - Egorova, Natalia; Shtyrov, Yury; Pulvermuller, Friedemann (Frontiers in Human Neuroscience, 2013)
Although language is a tool for communication, most research in the neuroscience of language has focused on studying words and sentences, while little is known about the brain mechanisms of speech acts, or communicative functions, for which words and sentences are used as tools. Here the neural processing of two types of speech acts, Naming and Requesting, was addressed using the time-resolved event-related potential (ERP) technique. The brain responses for Naming and Request diverged as early as ~120 ms after the onset of the critical words, at the same time as, or even before, the earliest brain manifestations of semantic word properties could be detected. Request-evoked potentials were generally larger in amplitude than those for Naming. The use of identical words in closely matched settings for both speech acts rules out explanation of the difference in terms of phonological, lexical, semantic properties, or word expectancy. The cortical sources underlying the ERP enhancement for Requests were found in the fronto-central cortex, consistent with the activation of action knowledge, as well as in the right temporo-parietal junction (TPJ), possibly reflecting additional implications of speech acts for social interaction and theory of mind. These results provide the first evidence for surprisingly early access to pragmatic and social interactive knowledge, which possibly occurs in parallel with other types of linguistic processing, and thus supports the near-simultaneous access to different subtypes of psycholinguistic information.